RESPONS HUKUM ISLAM TERHADAP PENGGUNAAN KECERDASAN BUATAN DALAM PRAKTIK KEAGAMAAN DI INDONESIA - Arif Fikri; Sawaluddin Siregar; Misbah Mardia (Yayasan Baitul Hikmah al-Zain, 2026)
The rapid development of artificial intelligence (AI) has increasingly influenced various aspects of social life, including religious practices among Muslim communities in Indonesia. The use of AI in religious contexts—such as Islamic question-and-answer applications, automated sermon and khutbah generation, religious text translation, and digital worship assistants—has raised normative and ethical debates regarding its legitimacy and legal boundaries within Islamic law. This article aims to examine the response of Islamic law to the use of artificial intelligence in religious practices in Indonesia by focusing on normative and ethical considerations. The study employs a qualitative normative–critical approach through document analysis of fatwas, contemporary scholarly opinions, relevant digital technology regulations, and previous research findings on AI and religion. The analysis is conducted using the frameworks of uṣūl al-fiqh and maqāṣid al-sharīʿah to assess the compatibility of AI applications with the fundamental principles of Islamic law. The findings indicate that Islamic law is generally receptive to the utilization of AI as a supportive tool in religious practices, provided that it does not replace scholarly authority, undermine core theological principles, or generate social and religious harm. Nevertheless, the use of AI in religious contexts requires clear normative boundaries and ethical oversight to prevent the erosion of religious meaning and scholarly legitimacy. This study underscores the need for an adaptive and critical Islamic legal framework to address the challenges posed by artificial intelligence in contemporary Indonesian religious life.